The Impact of Organizational Culture and Human Resource Development on Physiotherapist Performance - Praptiwi, Dewi; Cedaryana, C.; Sari, Rindi Nurlaila (Golden Ratio of Human Resource Management, 2025)
This qualitative research uses a case study approach to examine how the organizational culture and human resource development (HRD) initiatives impact the performance of physiotherapists at Klinik Bebas Cedera, PT Fisio Mitra Investasi. The data was obtained through detailed interviews with twelve physiotherapists from multiple branches, which were then analyzed thematically. The findings reveal that a culture that promotes professionalism, teamwork, and ongoing learning significantly enhances the performance of physiotherapists. Moreover, HRD programs such as training in dry needling and manual therapy improve technical competencies and increase self-confidence, resulting in improved patient care quality. Although the results are promising, the study highlights the importance of implementing consistent and comprehensive training across all branches to maintain performance gains. The research proposes strategies to reinforce organizational culture and HRD efforts to elevate the performance of physiotherapists further and improve service standards. This study offers valuable insights into how organizational elements can be optimized to advance health service outcomes.